2022
DOI: 10.1371/journal.pone.0267154
|View full text |Cite
|
Sign up to set email alerts
|

Masks, money, and mandates: A national survey on efforts to increase COVID-19 vaccination intentions in the United States

Abstract: Various efforts to increase COVID-19 vaccination rates have been employed in the United States. We sought to rapidly investigate public reactions to these efforts to increase vaccination, including self-reported responses to widespread reduced masking behavior, monetary incentive programs to get vaccinated, and work vaccination requirements. Using a unique method for data collection (Random Domain Intercept Technology), we captured a large (N = 14,152), broad-based sample of the United States Web-using populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…Such mandates have been politically contentious and variably effective. A large survey found that cash incentives such as gift cards and entry into lotteries would have no effect on the intentions of roughly half of unvaccinated U.S. adults and would make 40% of those who were disinclined to get a COVID-19 vaccine even less likely to get one 36 . The same survey found that 64% of those unvaccinated Americans who were not inclined to get a COVID-19 vaccine would not get one despite workplace requirements 36 .…”
Section: Covid-19 Vaccine Incentives and Mandatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such mandates have been politically contentious and variably effective. A large survey found that cash incentives such as gift cards and entry into lotteries would have no effect on the intentions of roughly half of unvaccinated U.S. adults and would make 40% of those who were disinclined to get a COVID-19 vaccine even less likely to get one 36 . The same survey found that 64% of those unvaccinated Americans who were not inclined to get a COVID-19 vaccine would not get one despite workplace requirements 36 .…”
Section: Covid-19 Vaccine Incentives and Mandatesmentioning
confidence: 99%
“…A large survey found that cash incentives such as gift cards and entry into lotteries would have no effect on the intentions of roughly half of unvaccinated U.S. adults and would make 40% of those who were disinclined to get a COVID-19 vaccine even less likely to get one 36 . The same survey found that 64% of those unvaccinated Americans who were not inclined to get a COVID-19 vaccine would not get one despite workplace requirements 36 . Despite opinion surveys suggesting that mandates may not be effective and vocal protests and legal actions against vaccine mandates, many entities, including corporations, colleges and universities, healthcare systems, and government agencies including the military saw significant increases in the numbers of vaccinated employees and students after the introduction of COVID-19 vaccine mandates 37 .…”
Section: Covid-19 Vaccine Incentives and Mandatesmentioning
confidence: 99%
“…Reitsma et al ( 2021 ) quantify how differential vaccine uptake by race and ethnicity within each U.S. state produced substantial vaccination coverage disparities during the initial scale-up among older adults. In terms of median household income, Sargent et al ( 2022 ) found those with annual household incomes greater than $50,001 were 1.5 times more likely to be vaccinated than those with lower incomes. A survey from Viswanath et al ( 2021 ) also showed that those with lower incomes were less likely to vaccinate people in their care than those with higher incomes.…”
Section: Covid-19 Disparities and Driversmentioning
confidence: 99%
“…Accurate and timely COVID-19 vaccination coverage data are vital for informing targeted, effective messaging and outreach and identifying barriers to equitable health service access. The tracking of vaccination rates is needed in conjunction with effective COVID-19 case surveillance and death monitoring, as well as research on predictors of vaccination uptake and vaccine hesitancy, to optimize vaccine coverage in persons at disproportionate risk of COVID-19 and severe outcomes [ 1 - 5 ]. However, gathering such vaccination rate data is challenging, even in high-income countries such as the United States.…”
Section: Introductionmentioning
confidence: 99%